A Structural Equation Model of Factors Affecting Tourism Business Competitive Advantage in the Andaman Coast - Na Phayap, Nutsana; Jankingthong, Wiwat; Thongpoon, Siriluck; Wangbenmad, Chutima (Economics and Business Administration Journal Thaksin University, 2024)
The purpose of this research is to examine a structural equation model of factors affecting the competitive advantage of the tourism business in Andaman coast. This research is quantitative research. The population is 1,978 tourism businesses in the Andaman coast area. The researcher used a simple sampling method and the sample size was 360 samples, the questionnaire was used as a tool for collecting data. Then the data were analyzed using the LISREL program version 11 version 11.0.3.2. The results of the analysis of factors affecting the effectiveness of the tourism business in southern Thailand was consistent with the empirical data, which found that RMSEA was 0.069, NNFI was 0.95, CFI was 0.90, and SRMR was 0.015. When considering the causal factors, it was found that innovation in business directly affects competitive advantage. Human capital management directly and indirectly affects competitive advantage through innovation in business. Adaptation in business directly affects competitive advantage and indirectly affects competitive advantage through innovation in business. The results of this research can be used as a guideline to develop the competitive advantage of the tourism business in the Andaman coast further.